2011
DOI: 10.1590/s1980-57642011dn05040010
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural Adaptation of the "Functional Activities Questionnaire - FAQ" for use in Brazil

Abstract: ObjectiveThe aim of this paper was to present the results of the first stage of cross-cultural adaptation of the Functional Activities Questionnaire (FAQ).MethodsThe tool was subjected to translation and re-translation, and the test-retest reliability of a proposed version for use in Brazil was analyzed.ResultsOf the 548 questionnaire respondents, a convenience sample of 68 informants was selected for retesting. Internal consistency was measured by Cronbach's alpha (0.95) while test-retest reliability was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
27

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 19 publications
2
41
0
27
Order By: Relevance
“…The Pfeffer Functional Activities Questionnaire seems to be one of the most commonly used tools for functional assessment aiming at the investigation of IADL performance. [7][8][9][10] One study using the Pfeffer scale 7 found an additive effect between functional scores and the Mini Mental State Examination (MMSE) for the diagnosis of AD. The Disability Assessment for Dementia was also adapted for Brazil 11 and seems to be useful for the characterization of functionality in frontotemporal dementia and AD, assessing both BADLs and IADLs as well as leisure activities, although these two groups do not show differences in functional performance.…”
Section: Introductionmentioning
confidence: 99%
“…The Pfeffer Functional Activities Questionnaire seems to be one of the most commonly used tools for functional assessment aiming at the investigation of IADL performance. [7][8][9][10] One study using the Pfeffer scale 7 found an additive effect between functional scores and the Mini Mental State Examination (MMSE) for the diagnosis of AD. The Disability Assessment for Dementia was also adapted for Brazil 11 and seems to be useful for the characterization of functionality in frontotemporal dementia and AD, assessing both BADLs and IADLs as well as leisure activities, although these two groups do not show differences in functional performance.…”
Section: Introductionmentioning
confidence: 99%
“…4 Além de apresentar potencial para ajudar profissionais na avaliação da saúde do idoso durante consultas e visitas domiciliares, o FAQ demanda breve tempo de aplicação. 5 Como instrumentos para aferição da capacidade funcional do idoso, com base no relato do informante, não estavam disponíveis para uso no Brasil, a adaptação transcultural do FAQ foi conduzida, a saber: equivalência conceitual, de itens, semântica e operacional; e avaliação de consistência interna e de confiabilidade. Essa versão brasileira do FAQ (FAQ-BR), aplicada ao informante, apresentou consistência interna de 0,95 (alfa de Cronbach) e coeficiente de correlação intraclasse de 0,97.…”
Section: Introductionunclassified
“…Essa versão brasileira do FAQ (FAQ-BR), aplicada ao informante, apresentou consistência interna de 0,95 (alfa de Cronbach) e coeficiente de correlação intraclasse de 0,97. 5 Estudo de revisão sobre o uso do FAQ no Brasil aponta que versões em português dessa escala, não submetidas a um processo formal de adaptação transcultural para o contexto brasileiro, têm sido muito utilizadas. 6 Embora tais versões tenham características semelhantes à original, sua estrutura foi alterada; além disso, avaliações sobre suas qualidades psicométricas não estavam disponí-veis até 2014, quando um estudo foi publicado com esse fim.…”
Section: Introductionunclassified
“…Além disso, a escala Cornell tem sido utilizada em ensaios clínicos que avaliam o efeito de fármacos no tratamento da depressão em demência (Lyketsos et al, 2003;Roose et al, 2003 (Pfeffer et al, 1982;Sanchez et al, 2011).…”
Section: Instrumentosunclassified